La literatura de los emigrantes políticos eslovenos después de la Segunda Guerra Mundial en Argentina - Geršak, Urša (Verba hispanica, 2014)
After the Second World War many political emigrants escaped from Slovenia to Argentina, among them leaders and soldiers of the home guard (belogardisti), sympathizers of the fascist forces, opponents of communism and their families, who were persecuted by the Yugoslav socialist regime. Among them were many intellectuals and artists, typically of right-wing political conviction and of Christian faith. In Argentina, they founded a hermetic community that kept the Slovenian language and traditional values, and hoped that one day they could return. People in the former Yugoslavia knew nothing about them or their activities or indeed about events after the war from the point of view of the Other. This paper reviews the historical circumstances that led to the emigration, the organization of the émigré community and their cultural life in Argentina, their literature, mainly novels and their ensconcement in another time and space, which is the time and space of memory and an idealized homeland. They were culturally very active and wrote mostly in Slovenian. It was not until the second generation and after Slovenia%s independence when they published several works in Spanish. Mostly they wrote historical novels, memoirs, dealing with unhealed wounds years after the Second World War, exile, life in refugee camps, post-war killings. Many of the works are ideologically laden, moralistic and idealizing life in Slovenia before the War. Due to their close community, literary works are often subject to some kind of "(self) censorship". Nevertheless, after Slovenia's independence, albeit with a delay, some of their works, because of their aesthetic and cultural values have become part of the national literatary canon and school textbooks.
Keywords: politična emigracija; izseljenska književnost; Argentina; antikomunizem; Slovene literature; slovenska književnost